2008
DOI: 10.1073/pnas.0803725105
|View full text |Cite
|
Sign up to set email alerts
|

Intralymphatic allergen administration renders specific immunotherapy faster and safer: A randomized controlled trial

Abstract: The only causative treatment for IgE-mediated allergies is allergenspecific immunotherapy. However, fewer than 5% of allergy patients receive immunotherapy because of its long duration and risk of allergic side effects. We aimed at enhancing s.c. immunotherapy by direct administration of allergen into s.c. lymph nodes. The objective was to evaluate safety and efficacy compared with conventional s.c. immunotherapy. In a monocentric open-label trial, 165 patients with grass pollen-induced rhinoconjunctivitis wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
328
4
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(364 citation statements)
references
References 20 publications
7
328
4
13
Order By: Relevance
“…Thus different approaches are under investigation to ameliorate this procedure, including optimization of antigens, new administration routes, and novel adjuvants. [3][4][5] Traditionally, subcutaneous SIT uses aluminum hydroxide, contributing to the formation of antigen depot at the inoculation site. In the mouse alum has been associated with the induction of T H 2 responses to coformulated antigens, even if its effects in human subjects are less clear.…”
mentioning
confidence: 99%
“…Thus different approaches are under investigation to ameliorate this procedure, including optimization of antigens, new administration routes, and novel adjuvants. [3][4][5] Traditionally, subcutaneous SIT uses aluminum hydroxide, contributing to the formation of antigen depot at the inoculation site. In the mouse alum has been associated with the induction of T H 2 responses to coformulated antigens, even if its effects in human subjects are less clear.…”
mentioning
confidence: 99%
“…We note that the clinical feasibility of LN injections in humans is well established from a number of clinical trials (2,8,9), and safe, injectable biomaterials are available that can encapsulate both small molecule and macromolecular cargos. These factors make the approach described here attractive as a general strategy for engineering the LN microenvironment not only for vaccination but also for therapeutic contexts, such as cancer immunotherapy or immunomodulation for allergy or autoimmune disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated as much as 10 6 -fold reductions in antigen dose (5,6), 100-fold reductions in adjuvant dose (7), and enhanced protection with reduced side effects relative to traditional parenteral immunizations (2). Lymph node injection in humans is readily performed using ultrasound guidance, and the promise of i.LN vaccination has been demonstrated in recent clinical trials (2,8,9).…”
mentioning
confidence: 99%
“…The results obtained in experimental models and in humans with allergy are essential, regarding the participation of hematopoietic mechanisms during the response to an allergenic (Denburg et al, 1998;Denburg & van Eeden, 2006, Sehmi et al, 1996Cyr & Denburg, 2001). In a comparative study with 153 patients with pollinic rhinoconjunctivitis, the effect of the administration of SIT either subcutaneously or intralymphatic was compared (Senti et al, 2008). In the later group, the administration of the pollinic allergen directly in a inguinal lymphatic ganglion using ultrasound as a control, with only three injections separated by 4 weeks, in the response to a specific nasal induction 4 months after the last administration, required a dosage ten times higher than the one required in patients under SCIT treatment for three years and with a cumulative dosage drastically higher and with multiple allergenic injections.…”
Section: Involvement Of the Organs From The Immune Systemmentioning
confidence: 99%